1996
DOI: 10.3171/jns.1996.85.3.0410
|View full text |Cite
|
Sign up to set email alerts
|

Age and outcome after aneurysmal subarachnoid hemorrhage: why do older patients fare worse?

Abstract: Advanced age is a recognized prognostic indicator of poor outcome after subarachnoid hemorrhage (SAH). The relationship of age to other prognostic factors and outcome was evaluated using data from the multicenter randomized trial of nicardipine in SAH conducted in 21 neurosurgical centers in North America. Among the 906 patients who were studied, five different age groups were considered: 40 years or less, 41 to 50, 51 to 60, 61 to 70, and more than 71 years. Twenty-three percent of the individuals enrolled we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
157
4
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(190 citation statements)
references
References 43 publications
19
157
4
10
Order By: Relevance
“…19) The male dominance among patients with SAH has been observed in childhood and adolescence, whereas the female preponderance with male to female ratio of 2:1 is frequently observed in adult group of patients. 6,9,20) The reports on the sex dominance in young adults are variable. 5,7,11,14,21) A slight male dominance was noted (58.3%) in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19) The male dominance among patients with SAH has been observed in childhood and adolescence, whereas the female preponderance with male to female ratio of 2:1 is frequently observed in adult group of patients. 6,9,20) The reports on the sex dominance in young adults are variable. 5,7,11,14,21) A slight male dominance was noted (58.3%) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…16) Old age and female sex are strong predictors of poor outcome in the general population. 9) Studies discussing outcomes of aneurysmal SAH in young adults have demonstrated favorable outcomes in this subgroup of patients. 5,7,11,14,21) As these patients continue to improve after discharge, vigilant supportive and rehabilitation care should be emphasized to ensure the optimal recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Aging probably is one of the most significant independent factors. It impairs several physiologic patterns related to cerebrovascular hemodynamics and homeostasis 6,7,8,9,10,11,12 . There is a decline in cerebral blood flow velocity with age, which may be associated with certain changes as: decreased cerebral blood flow (CBF) or metabolic demands; vessel changes like progressive kinking, calcifications (Figure 4), elongation, stenosis and lower cardiac output 1,2,3,11,13,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…All those statements justify that elderly usually present with more severe SAH than younger patients, characterized by higher Fisher and Hunt Hess grades. After treatment, elderly are also prone to face severe neurological and systemic complications, like vasospasm, hydrocephalus, brain and heart ischemic insults and others 6,7,8,9,10 . Cerebral vasospasm (VSP) is the major complication associated with aneurysmal SAH that results in delayed ischemic deficits in up to 25% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior studies demonstrating an association between younger age and more favorable outcomes following SAH. 10,11,14,20,24,31 Although patients 65 years of age or younger had more than 5 times the odds of improvement beyond 6 months, when improvement specific to the time intervals beyond 1 year was analyzed, age was no longer a significant predictor. This finding suggests that while younger age has its benefits in recovery, the most delayed improvement is driven primarily by other factors.…”
Section: Figmentioning
confidence: 99%